Hygroscopic properties of atmospheric particles emitted during wintertime biomass burning episodes in Athens. (April 2018) - Psichoudaki, Magda; Nenes, Athanasios; Florou, Kalliopi; Kaltsonoudis, Christos; Pandis, Spyros N.
Abstract: This study explores the Cloud Condensation Nuclei (CCN) activity of atmospheric particles during intense biomass burning periods in an urban environment. During a one-month campaign in the center of Athens, Greece, a CCN counter coupled with a Scanning Mobility Particle Sizer (SMPS) and a high resolution Aerosol Mass Spectrometer (HR-AMS) were used to measure the size-resolved CCN activity and composition of the atmospheric aerosols. During the day, the organic fraction of the particles was more than 50%, reaching almost 80% at night, when the fireplaces were used. Positive Matrix Factorization (PMF) analysis revealed 4 factors with biomass burning being the dominant source after 18:00 until the early morning. The CCN-based overall hygroscopicity parameter κ ranged from 0.15 to 0.25. During the night, when the biomass burning organic aerosol (bbOA) dominated, the hygroscopicity parameter for the mixed organic/inorganic particles was on average 0.16. The hygroscopicity of the biomass-burning organic particles was 0.09, while the corresponding average value for all organic particulate matter during the campaign was 0.12. Highlights: Hygroscopicity of biomass burning organic aerosol from residential combustion studied. The hygroscopicity parameter of the biomass burning organic aerosol was 0.09. Biomass burning organic aerosol dominated during the night in Athens.